Critical Approaches to Ideological and Political Education: Building Effective Classroom Strategies with New Media Support for Psychological Engagement in Sports - Kanghui Qin; Chenjiao Liu; Yan Li; Tingli Liu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
New media have become essential tools for fostering psychological engagement and effective communication in educational fields, including ideological and political education. By integrating mainstream media, information dissemination, and interactive platforms, new media not only enhance communication techniques but also transform the mechanisms of influence in shaping ideologies and behaviors. To advance research in this area, it is critical to explore the psychological underpinnings of new media’s role in ideological and political education, drawing on principles of motivation, social interaction, and cognitive engagement, while situating these within Marxist coexistence, political communication frameworks, and traditional systems of governance. Classroom teaching logic in this context focuses on the psychological and relational dynamics between educators, learners, and mediators, fostering associations and reasoning tailored to modern educational needs. The transformation of teaching approaches involves adopting embodied, intelligent methods that engage learners both cognitively and emotionally. Simultaneously, curriculum culture evolves from passive consumption to active value creation, promoting psychological growth and resilience. By integrating course content with these dynamic frameworks, new media-driven education can foster a deeper connection, enhancing the psychological impact of ideological and political education. These insights can also inform sports psychology, particularly in developing strategies for motivation, group cohesion, and cognitive engagement in athletic and team settings.